Implementasi Media Flash Card untuk Meningkatkan Motivasi Belajar Peserta Didik Materi Fakta dan Opini Kelas IV Di SDN Gili Timur 1 Kamal (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This research is motivated by the lack of student motivation in learning Indonesian, which is due to the limited availability of innovative learning media. Additionally, this research is tailored to the abilities of the students. The purpose of this study is to determine the level of student motivation in using flash card media in Indonesian language subjects at the elementary school level. The method used is a qualitative approach by conducting field research, with data obtained through observation, interviews, documentation, analysis, reduction, presentation, and data verification. The results of the study indicate that the use of flash card media can enhance student motivation in learning materials on facts and opinions, create an enjoyable classroom atmosphere, and foster student enthusiasm. Moreover, it helps students become more actively engaged in the learning process.